2017
DOI: 10.1111/ocr.12212
|View full text |Cite
|
Sign up to set email alerts
|

Effects of loading on chondrocyte hypoxia, HIF‐1α and VEGF in the mandibular condylar cartilage of young rats

Abstract: Mechanical loading seems to directly induce weight-bearing area hypoxia followed by new vessel formation, which indicates that these factors are related and important for the development of cartilage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 33 publications
3
17
0
Order By: Relevance
“…Module 2 including hub gene insulinlike growth factor 1 (IGF1) and vascular endothelial growth factor (VEGF) was associated with "platelet degranulation", "protein processing", "regulation of protein secretion" and "apoptotic signaling pathway". These results are consistent with the previous studies indicating that mechanical loading directly induce weight-bearing area hypoxia followed by upregulated expression of VEGF [32], Shear stress induced the activation of IGF1 pathway which involved in the regulation of morphology and proliferation in the chondrocytes [33], and even IGF-1 has been shown to protect chondrocytes from apoptosis [34]. [35,36].…”
Section: Discussionsupporting
confidence: 93%
“…Module 2 including hub gene insulinlike growth factor 1 (IGF1) and vascular endothelial growth factor (VEGF) was associated with "platelet degranulation", "protein processing", "regulation of protein secretion" and "apoptotic signaling pathway". These results are consistent with the previous studies indicating that mechanical loading directly induce weight-bearing area hypoxia followed by upregulated expression of VEGF [32], Shear stress induced the activation of IGF1 pathway which involved in the regulation of morphology and proliferation in the chondrocytes [33], and even IGF-1 has been shown to protect chondrocytes from apoptosis [34]. [35,36].…”
Section: Discussionsupporting
confidence: 93%
“…Hypoxyprobe-1, a type of pimonidazole hydrochloride, was used asa specific marker for hypoxia [ 14 ]. The immunohistochemistry results showed that the expression areas for Hypoxyprobe-1 and HIF-1α ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Hypoxia is not only a consequence of unrestrained fast tumor growth; it also plays a vital role in promoting tumor proliferation, invasion, EMT, distant metastasis and resistance to therapy [ [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] ]. The tumor stroma is a dynamic environment, which includes inflammatory cells, pancreatic stellate cells (PSC), endothelial cells, extracellular matrix (ECM), growth factors and cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis and pathophysiology of OA remain unclear, which creates obstacles in studying the development and progression of OA ( 9 ). Numerous studies have reported on the involvement of VEGF in the degenerative progression of cartilage ( 19 – 21 ). Angiogenic inhibitors are produced by normal articular cartilage, which, consequently, lack vascular tissue ( 4 ).…”
Section: Discussionmentioning
confidence: 99%